2015
DOI: 10.1089/acm.2014.0186
|View full text |Cite
|
Sign up to set email alerts
|

Manual and Electrical Needle Stimulation in Acupuncture Research: Pitfalls and Challenges of Heterogeneity

Abstract: In the field of acupuncture research there is an implicit yet unexplored assumption that the evidence on manual and electrical stimulation techniques, derived from basic science studies, clinical trials, systematic reviews, and meta-analyses, is generally interchangeable. Such interchangeability would justify a bidirectional approach to acupuncture research, where basic science studies and clinical trials each inform the other. This article examines the validity of this fundamental assumption by critically rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 64 publications
1
89
0
1
Order By: Relevance
“…A recent white paper by Langevin and colleagues highlighted the inherent difficulties in comparing MA and EA, as all of the included trials that used EA obtained de qi via manual stimulation before the addition of EA; therefore, the included studies may be more accurately interpreted as comparing MA versus MA+EA rather than MA versus EA. 31 The importance of de qi in treating menstrual pain is still unclear; while Xiong 26 found an effect on immediate menstrual pain, a more recent analysis on the importance of de qi in the treatment of primary dysmenorrhoea casts doubt on this finding. 32 When considering the number of needles used, there were no obvious dose-response relationship across studies; interestingly, however, one study suggested that treatment using a single needle during menses may give better results, whereas multiple needles may be superior before menses.…”
Section: Immediatementioning
confidence: 99%
“…A recent white paper by Langevin and colleagues highlighted the inherent difficulties in comparing MA and EA, as all of the included trials that used EA obtained de qi via manual stimulation before the addition of EA; therefore, the included studies may be more accurately interpreted as comparing MA versus MA+EA rather than MA versus EA. 31 The importance of de qi in treating menstrual pain is still unclear; while Xiong 26 found an effect on immediate menstrual pain, a more recent analysis on the importance of de qi in the treatment of primary dysmenorrhoea casts doubt on this finding. 32 When considering the number of needles used, there were no obvious dose-response relationship across studies; interestingly, however, one study suggested that treatment using a single needle during menses may give better results, whereas multiple needles may be superior before menses.…”
Section: Immediatementioning
confidence: 99%
“…It is perhaps worth pointing out that RCTs from the acupuncture literature achieve better analgesia by adding electricity than by brief or intermittent manual stimulation alone [132]. While only one systematic review has directly compared …”
Section: Calcitonin Gene Regulated Peptide and Substance-pmentioning
confidence: 99%
“…Acupuncture is a minimallyinvasive therapeutic modality that originated in China 2000 years ago as a component of traditional Chinese medicine (Kaptchuk, 2002). While acupuncture therapy is rooted in a complex practice ritual, the acupuncture needle procedure, particularly when coupled with electrical needle stimulation, overlaps significantly with many conventional peripheral neuromodulatory therapies (Langevin et al, 2015) that have generated significant excitement as 'electroceuticals' targeting peripheral nerve receptors (Famm et al, 2013;Waltz, 2016). However, the neurophysiological mechanisms by which acupuncture impacts subjective/psychological (i.e.…”
Section: Introductionmentioning
confidence: 99%